Musicoterapia na reabilitação de funções cognitivas de paciente com lesão cerebral - Vargas, Maryléa Elizabeth Ramos (2011)
Present in all cultures, whether to celebrate, praise or register ceremonial music brand history. It records meetings, disagreements and historical situations, makes present what is absent and automatically connects our memory of past events. This paper, with focus in the practical intentions of social and the care, aims to present the research done on investigating the applicability of the musical language resources to promote the rehabilitation of cognitive function in patients with brain injury. The young participants of the case study, hemiplegic due to car accident in October 2007, presents difficulties in different orders, because of physical limitations has aggregated cognitive limitations. When considering the range of complaints relevant to a weakness in memory in the acquisition of new data and in its setting the research was drawn in order to investigate the feasibility of obtaining the musical language through music therapy in a resource to minimize such damage. To meet the purposes outlined investigated the possibility of memory acquisition by offering new songs in context with music. The music therapy sessions for this purpose were recorded over the 16 meetings that took place at intervals of twice a week during the second half of 2010. To address this proposal and in compliance with Resolution 196/96, which deals with human research, we designed a research protocol approved by the CEP Faculdades EST. This paper presents the results of research conducted in addition to meeting the development of Monograph in Master of Professional Researcher. In pursuit of meeting the objectives outlined and articulated to the practice performance, sustained research into the theoretical bases of Music Therapy, Music and neuroscience. It can be observed that the application of the musical language in the context music therapeutic established itself as an aid to writing new content, presenting itself as a facilitator for memorization. The research participant, despite the difficulty in meeting the melodic contour of the songs presented frank suggested condition to memorize the text, noting that the use of music is stimulating element for the establishment of new content.